GROW OUT AND EVALUATION OF FIRST GENERATION (F1) OF PROSPECTIVE HUMPBACK GROUPER Cromileptes altivelis BROODSTOCK - . Tridjoko; Ida Komang Wardana; Ahmad Muzaki (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
During this time the humpback grouper broodstock spawning that comes from nature. Efforts to provide humpback grouper fish from cultured (F1) has been conducted and it has been spawn. The purpose of this study was to determine the quality of broodstock first generation (F1) with a good maintenance management and monitoring evaluation of character growth, gonad development, and genetic characteristics through microsatelite marker. Broodstock reared in concrete tank volume of 75 m3 with three different of hormonal implantation treatments: (1) estradiol, (2) 17α-methyltestosterone (MT), (3) a mixture of 17α-Methyl-testosterone by aromatase inhibitors, and control. The observed parameters were growth, gonad development, reproductive hormones in the blood composition and the performance of genetic through microsatellite analysis. The results showed that the humpback grouper F1 implantation treatment by methyl testosterone and estradiol showed good growth with an average body weight at the end of the observed ranged from 680 ± 60.5 to 820 ± 76,5g with an average body length of 34 -36 cm. In individual control growth better because during the maintenance of the population is not implanted. Analyses of testosterone and estradiol in the blood plasma showed that 40% of individuals in the population were males. Microsatellite analysis showed that F1 fish had good genetic variation (0.778-1.000) so that it can be used as broodstock candidate.